Auditoría de gestión a la Fundación CISOL (Centro de iniciativas sociales Latinoamericanas) de la Ciudad de Loja, periodo 01 de enero al 31 de diciembre del 2014 - Montaño Armijos, Rosa Alexandra (2016)
The object of study of this thesis is the application of an "AUDIT MANAGEMENT TO THE CISOL FOUNDATION (LATIN AMERICAN SOCIAL INITIATIVES CENTER) OF THE CITY OF SHOP, PERIOD 01 JANUARY TO DECEMBER 31, 2014", was carried out as Requisite for obtaining the title of Engineer in Accounting and Auditing Public Accountant-Auditor. For that, the present thesis was developed in the same one that was proposed: to evaluate the internal control of the Foundation through the Management Audit to determine the critical areas for which the internal control questionnaire was applied to the Human Talent and Financial Resources component with Which determined a high level of confidence and low risk, and established that there are some shortcomings in the activities carried out by the foundation, which are detailed in their respective narrative notes. Management indicators were also used to measure the degree of efficiency and effectiveness to know the proper management of the economic resources of each project. Thus, it was possible to show that in the period 2014 a budget deficit was obtained in the CISOL Project of $ 2,764, 45 which was the indicator that most stood out. Finally, the Final Audit Report was issued, and the follow-up schedule that was made based on the existing regulations governing the Foundation and the other procedures included in the Management Audit Manual. 5 According to the results obtained in the Thesis, it was determined that the Cisol Foundation did not apply Management Audits, on the other hand there is no Human Talent Department, the Strategic Plan has not been made available to recently hired personnel, Inadequate separation of functions, and staff evaluations have not been carried out. In view of this, the CISOL Foundation was recommended to carry out Management Audits on a regular basis and to carry out evaluations to the staff that will enable them to know the efficiency with which they carry out their work, and also to prepare a training plan to help improve the deficiencies of the activities carried out.